THE EFFECT OF DOUBLE-SKIN FACADEâS GLASS TILT ANGLE ON INTERNAL HEAT GAIN: BANDUNG AS CASE STUDY - Darmayanty, Nuraini
The façade became the thermal transfer highlight when the outer wall area were greater than the roof area, such as in tall buildings. Double-skin façade (DSF) system had potential to serve as thermal control measure by filtering solar radiation and consequently avoiding the heat gain. Through researches, the performance of DSF system was recognized based on its configuration and climate context. DSF performed a complex thermal phenomenon, which included the optical process through glass layers, the thermodynamic process, and the fluid dynamic process inside its cavity. DSF as heating avoidance measures was the discussion of this thesis, and took focus on its optical and thermodynamic process. This research was conducted in order to gain knowledge on building’s facade design alternatives that prevented heat gain by a responsive approach towards direct solar radiation. With predefined configuration depended on local latitude, DSF’s outer glass layer was utilized as direct solar radiation filter while maintaining transparent and light architectural expression. Local latitude and coordinates were important to determine the local direct solar radiation intensity, the angle of solar incidence, the horizontal shadow angle (HSA) and vertical shadow angle (VSA) for all building orientations. In equatorial region, direct vertical solar radiation intensity received on east and west facade was far greater than on north and south facade. Therefore, the selected case study was located in Bandung and set to be responsive towards solar radiation on east facade. In order to investigate the effect of DSF’s glass configuration angle on internal heat gain, field experiment on full-scale hypothetical models were conducted. Hypothetical DSF models were constructed in following steps: (1) Analyzing direct solar radiation intensity in Bandung to determine yearly and hourly critical time when radiation should be avoided. (2) Analyzing solar angle of incidence specific to point (1). (3) Analyzing DSF’s outer glass configuration angle to respond the solar incidence by applying total internal reflection theory – total internal reflection happened when the angle of incidence was larger than the medium's critical angle. Medium critical angle set by its reflective index (glass reflective index was 1.5, glass critical angle was 42°). (4) Design optimation process which developed models into four prototypes. Hypothetical model DSF 1 was optimized based on yearly direct normal solar radiation intensity and positioned to reflect 09:00 AM, 10:00 AM and 11:00 AM VSAs. Hypothetical model DSF 2 was optimized based on yearly direct normal solar radiation intensity and positioned to reflect 10:00 AM VSA. Hypothetical model DSF 3 was optimized based on yearly direct normal solar radiation intensity and positioned to reflect 08:00 AM VSA and hourly HSA at exact experiment time. Hypothetical model DSF 4 was designed to be an adjustable prototype which reflected VSA and HSA at exact experiment time. Experiment on four DSF prototypes were conducted on October 22 - 24, 2013, tested at similar condition and at the same direct solar radiation exposure. The effect of DSF’s outer glass configuration angle on internal heat gain was examined through internal radiant globe temperature comparison between Non-DSF condition and with-DSF condition. Internal radiant globe temperature was considered reliable as the representation of internal heat gain. The test result showed that DSF’s tilt angle gave effect on decreasing internal heat gain that came from solar radiation through fenestration. DSF performance in decreasing and evenly distributing the internal heat gain was consistent, whether the sky was clear or overcast. DSF significantly reduced internal heat gain when the sky was clear. DSF’s outer glass tilt angle relative to sun altitude showed correlation with internal heat gain. The lesser the angle formed between glass plane normal and sun altitude, the greater the heat gain reduction. Correlation and regression analysis were conducted upon experiment data and resulted in the fact that the angle formed between glass plane normal and VSA (??) was strongly correlated to the performance of DSF models in decreasing the globe temperature. The lesser the ?? angle at a certain time, the greater the globe temperature decrease at that time. The angle formed between glass plane normal and HSA (??) was weakly correlated to the performance of DSF models in decreasing the globe temperature. DSF 1, which formed various ?? angles and relatively small ?? angles in the morning to afternoon, performed the best daily average in decreasing and distributing heat gain. DSF 2 and DSF 3 showed second and third best performance. Whereas the adjustable DSF 4, the hourly positioned so its critical angle (at 42°) always met with VSA and HSA, resulted the least globe temperature decrease. DSF 4 performed better than DSF 2 and DSF 3 at 10:00 am to 12:00 pm, when its glass position formed smaller ?? angles than DSF 2 and DSF 3 at the same time range. Evaluation on the 42° critical angle that was presumed during hypothetical model design phase was necessary should DSF 4 performance before 10:00 am was to be improved.